Web-Based Financial Information System at Digimizu Digital Management - Titin Listiani; Eko Purwanto; Hanifah Permatasari (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Digimizu Digital Management specializes in Software and Photography as well as Digital Content while delivering on-demand services. The company operates without a computerized information system for managing both transactions and financial reports. The company handles orders manually via WhatsApp or face-to-face interactions while transaction records are kept on paper and within Microsoft Excel files. Data loss becomes possible alongside human errors and inaccurate reporting while real-time data access and monitoring face constraints. The company needs a web-based financial information system which should combine transaction automation with customer data management functions alongside quick and accurate financial report generation. The development of the financial information system utilizes the SDLC method with the Waterfall model and system weaknesses analysis through the PIECES method with UML (Unified Modeling Language) support. This system implementation will bring efficiency to Digimizu Digital Management's business procedures while decreasing errors in recording and enabling real-time financial activity tracking which will enhance overall company performance.